Assessing fine-scale diel movement patterns of an exploited coral reef fish. Issue 1 (December 2015) - Currey, Leanne; Heupel, Michelle; Simpfendorfer, Colin; Williams, Ashley
Abstract Background Understanding movement patterns of species requires that the spatial and temporal scales of experimental designs are appropriate to the proposed ecological questions. Previous research on large-scale movements of the exploited reef fishLethrinus miniatus suggested that adult individuals may use coral reef slope habitat during the day, shifting to adjacent deeper sandy habitat at night. However, investigation of movement at a fine spatial and temporal scale is required to verify this diel activity pattern. Using a closely positioned acoustic telemetry system, movements of 11L. miniatus were monitored among habitats from the reef crest, to reef slope and deeper adjacent sandy habitat over 3 months. Fine-scale movement patterns among these habitats were compared among four different 3 h periods of the day: dawn, day, dusk and night. Results Initial observations demonstrated significantly larger horizontal core areas and vertical areas of extent during crepuscular and night periods compared to during the day. Vertical space use (core area and extent) was consistently larger during dawn, dusk and night compared to during the day. Area of activity space extent within the water column and proportional overlap among areas used during different periods of the day varied among weeks, and displayed a pattern consistent with full moon periods. Conclusions Although previous evidence suggested thatL. miniatus adults may shift to deeper habitats adjacent to the reef slope at night, greater space use across the shallow crest to deeper sand habitat was observed during dawn, dusk and night periods. Increased luminosity during dawn, dusk and night periods may causeL. miniatus to utilise a larger search area for foraging. While further research is required to confirm foraging during the hours of twilight and darkness, this fine-scale approach identified patterns in nocturnal activity for an important reef teleost. Knowledge of these temporal and spatial differences inL. miniatus behaviour and movement are important to understanding how this species coexists within ecological niches.